KATA-KATA TABU DALAM FILM BAD BOYS II KARYA MICHAEL BAY (SUATU ANALISIS SOSIOLINGUISTIK) - TUMENO, NOVITA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT Â This research is entitled â€œTaboo Words in the film Bad Boys II by Michael Bay A Sociolinguistic Analysisâ€. The objectives of this research are identify, classify, and analyze the types of taboo words.Â This research uses a descriptive method. There are were three steps to finish this research, the first step is preparation, the data taboo words in the film Bad Boys II were taken from internet and understanding the movie script, also read some books like journal and skripsi. The second step the writer watches Bad Boys II movie, printed script of the movie, then the writer reads the script and find out the conversations that contain taboo words. The third step is the data were analyzed using theory of Wardhaugh uses seven types of taboo words (1986). The results of this research show that there are 103 taboo words found in Bad Boys II. According to theory of Wardhaugh, there are seven types of taboo words, those are taboo words related to mother in law, animal, sex, death, excretion, bodily function, and religion. The findings of this research support the theory of Wardhaugh. Â Keywords: Taboo Words, Movie: Bad Boys II, theory: Wardhaugh; SociolinguisticAnalysis